Modern methods of surgical rehabilitation of patients adhesion deformation or absence of the conjunctival cavity in anophthalmos - Yakimenko , S. A.; Kostenko , P. A. (Ukrainian Journal of Ophthalmology, 2026)
Modern methods of surgical rehabilitation of patients adhesion deformation or absence of the conjunctival cavity in anophthalmos